Empirical Analysis of Renewable Energy Demand in Ghana with Autometrics - Ackah, Ishmael; Asomani, Mcmori (International Journal of Energy Economics and Policy, 2015)
Increased investment in renewable energy has been identified as a potential solution to the intermittent power supply in Ghana. Recently, a Renewable Energy Act has been passed which has a target of 10% of renewable energy component in Ghana’s energy mix by 2020. Whilst effort is been made to enhance supply through feed in tariffs, education and tax reduction on renewable energy related equipment, there is the need to understand the drivers of renewable energy demand. Due to dearth of studies on renewable energy demand in Ghana, this study seeks to fill both policy and research gap on renewable demand trend in Ghana. In this study, the general unrestricted model through Autometrics is used to estimate the determinants of renewable energy demand in Ghana. The results indicate that both economic factors and non-economic affect the demand for renewable energy. In addition, the underlying energy demand trend exhibits energy using behaviour. The study recommends that economic factors such as consumer subsidies should be considered when promoting renewable energy demand. Keywords: Renewable energy; energy consumption; Autometrics; Ghana JEL Classifications: Q41; Q42; Q43